1997
DOI: 10.1073/pnas.94.25.13618
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and cell cycle regulation of the related human telomeric proteins Pin2 and TRF1 suggest a role in mitosis

Abstract: Telomeres are essential for preserving chromosome integrity during the cell cycle and have been specifically implicated in mitotic progression, but little is known about the signaling molecule(s) involved. The human telomeric repeat binding factor protein (TRF1) is shown to be important in regulating telomere length. However, nothing is known about its function and regulation during the cell cycle. The sequence of PIN2, one of three human genes (PIN1-3) we previously cloned whose products interact with the Asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(137 citation statements)
references
References 39 publications
7
130
0
Order By: Relevance
“…[117][118][119][120][121][122] Dr Kun Ping Lu (Harvard University, Boston, MA, USA) described techniques to isolate the Pin genes encoding these proteins and discussed how these low molecular weight proteins belong to a large multi-gene family. Pin proteins are peptidyl-prolyl cis/trans isomerases (PPIase).…”
Section: Regulatory Proteins Which Recognize and Bind Serine Threoninmentioning
confidence: 99%
“…[117][118][119][120][121][122] Dr Kun Ping Lu (Harvard University, Boston, MA, USA) described techniques to isolate the Pin genes encoding these proteins and discussed how these low molecular weight proteins belong to a large multi-gene family. Pin proteins are peptidyl-prolyl cis/trans isomerases (PPIase).…”
Section: Regulatory Proteins Which Recognize and Bind Serine Threoninmentioning
confidence: 99%
“…Transfected living cells were monitored over time and ®xed at various time points. The indexes of interphase, mitotic and apoptotic cells were determined after staining the cells with the DNA-binding dye DAPI or the mitosis-speci®c monoclonal antibody MPM-2, as described (Lu and Hunter, 1995;Shen et al, 1997). The apoptosis rate was determined by counting about 300 ± 400 GFP-positive cells.…”
Section: Transient Transfection and Apoptosis Assaysmentioning
confidence: 99%
“…TRF1 and Pin2 are likely two alternatively spliced isoforms of the same gene PIN2/ TRF1, as suggested by Young et al (1997). For clarity, we will here use Pin2 for the 20 amino acid deletion isoform and TRF1 for the 20 amino acid containing isoform, as they were originally identi®ed (Chong et al, 1995;Shen et al 1997), and will refer to the endogenous Pin2 and TRF1 proteins as Pin2/TRF1 since it is di cult to physically or functionally separate these isoforms at the present time. However, we have shown that Pin2 is 5 ± 10-fold more abundant than TRF1 in the cells and the expression level of Pin2/ TRF1 is tightly regulated during the cell cycle .…”
Section: Introductionmentioning
confidence: 99%
“…We were interested to determine if Chinese hamster cells have genes that express telomere repeat binding factors and whether they are seen at chromosome ends. Recently, human and mouse telomere binding proteins (TRF1, TRF2 and PIN2) have been identi®ed (Bilaud et al, 1996(Bilaud et al, , 1997Broccoli et al, 1997a,b;Shen et al, 1997;Chong et al, 1995). The TRF1 gene has been implicated in the regulation of telomere length (van Steensel and de Lange, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian telomeres contain long arrays of TTAGGG repeats that are bound with specialized protein complexes and have several functions (Moyzis et al, 1988;Meyne et al, 1989;Zakian, 1996;Greider, 1996). Three telomere binding proteins namely, TRF1, TRF2 and PIN2 have been identi®ed (Bilaud et al, 1996(Bilaud et al, , 1997Broccoli et al, 1997a,b;Shen et al, 1997;Chong et al, 1995, Zhong et al, 1992. They have DNA binding properties with TTAGGG repeats in vitro irrespective of the presence of a DNA terminus, properties which are consistent with its presence along the ends of chromosomes.…”
Section: Introductionmentioning
confidence: 98%